The Minimalist and Maximalist Approaches in the TEFLIN: Towards the Empowerment of the General Indonesian Learners of English - Asim Gunarwan (TEFLIN Journal: A publication on the teaching and learning of English, 2001)
Abstract: The point of departure of this paper is an assumption that the teaching of English in Indonesian public schools has not yielded the minimum expected result: English learners have not been empowered with the reading skill in English, let alone the other skills. Given that English has an elevated role to play in the new millennium, Indonesian learners should be empowered in this language for wider communicaÃÂtions. Two approaches are proposed, namely (1) the minimalist approach, in which reading ability is the sole objective of the teaching of English to students in general, the corrolary being the use of the translation method; and (2) the maximalist approach, in which "ordinary" students are taught along the line of the notion of Little English (much discussed in the 60s and 70s), whereas "the cream of the cream" are tutored in a special programme designed to make them English-Indonesian bilinguals. Hence, a new language policy of Indonesia should be developed and English curricula be reviewed and a national commission on the TEFLIN be set up to look into the matter in more depth and to suggest ways in which the teaching of this language in schools can really empower the learners in the context of human resources development.